2020
DOI: 10.1371/journal.pone.0228179
|View full text |Cite
|
Sign up to set email alerts
|

Compared to other front-of-pack nutrition labels, the Nutri-Score emerged as the most efficient to inform Swiss consumers on the nutritional quality of food products

Abstract: Background Switzerland, like other high-income countries, is facing a major public health challenge with the increasing burden of non-communicable diseases. Discussions are currently ongoing in Switzerland regarding the implementation of a Front-of-Pack nutrition label (FoPL) as a public health measure to guide consumers towards healthier food choices, and the Nutri-Score represents an alternative supported by multiple actors. To date, no studies have investigated the performance of the Nutri-Score among Swiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 67 publications
(76 reference statements)
5
26
2
3
Order By: Relevance
“…Compared to the RIs, the Nutri-Score was the FoPL that produced the largest increase in participants' ability to correctly rank the nutritional quality of products, followed by the HSR. These results are consistent with the findings based on the FOP-ICE study, where the Nutri-Score was observed as the best scheme to help participants identify the nutritional quality of products in different countries, including European countries: Belgium, Bulgaria, Denmark, France, Germany, Spain, Switzerland, the Netherlands and the United Kingdom [19,22,25,26]. Notably, similar results were observed in Spain, another Mediterranean country with a similar food context and dietary behaviors as Italy [19].…”
Section: Discussionsupporting
confidence: 90%
“…Compared to the RIs, the Nutri-Score was the FoPL that produced the largest increase in participants' ability to correctly rank the nutritional quality of products, followed by the HSR. These results are consistent with the findings based on the FOP-ICE study, where the Nutri-Score was observed as the best scheme to help participants identify the nutritional quality of products in different countries, including European countries: Belgium, Bulgaria, Denmark, France, Germany, Spain, Switzerland, the Netherlands and the United Kingdom [19,22,25,26]. Notably, similar results were observed in Spain, another Mediterranean country with a similar food context and dietary behaviors as Italy [19].…”
Section: Discussionsupporting
confidence: 90%
“…While the exact effect size of food labeling on the consumption of foods with added sugar remains unclear, the Nutri-Score scheme was found to have greater effects on German consumers’ behavior than other types of food labels (Egnell et al 2018). Considering that Nutri-Score was recently reported to effectuate a 10.6% improvement in food choices away from sugar-containing products (Egnell et al 2020), and such an effect size is larger than assumed in our model, our findings might be considered lower-bound estimates for the impact of Nutri-Score on reducing sugar-attributable caries burdens.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, it has been observed that consumer do not consult food label information at time of purchase due to education, lack of confidence and lifestyle. Studies have suggested examining the effectiveness of food label information for the selection of right amount of nutrients (Egnell et al, 2020;Ajmal & Kumar, 2021). Although food processing companies are promoting healthy food awareness with food label information but majority of consumer consider food label as marketing tool.…”
Section: Review Of Related Literaturementioning
confidence: 99%